A review of train aerodynamics Part 2 – Applications. (April 2014) - Baker, C. J.
Abstract: This paper is the second part of a two-part paper that presents a wide-ranging review of train aerodynamics. Part 1 presented a detailed description of the flow field around the train and identified a number of flow regions. The effect of cross winds and flow confinement was also discussed. Based on this basic understanding, this paper then addresses a number of issues that are of concern in the design and operation of modern trains. These include aerodynamic resistance and energy consumption, aerodynamic loads on trackside structures, the safety of passengers and trackside workers in train slipstreams, the flight of ballast beneath trains, the overturning of trains in high winds and the issues associated with trains passing through tunnels. Brief conclusions are drawn regarding the need to establish a consistent risk based framework for aerodynamic effects.